Lactobacillus reuteri LR1 Improved Expression of Genes of Tight Junction Proteins via the MLCK Pathway in IPEC-1 Cells during Infection with Enterotoxigenic Escherichia coli K88 - Hongbo Yi; Li Wang; Yunxia Xiong; Zhilin Wang; Yueqin Qiu; Xiaolu Wen; Zongyong Jiang; Xuefen Yang; Xianyong Ma (Mediators of Inflammation)
Intestinal epithelial barrier damage disrupts immune homeostasis and leads to many intestinal disorders. Lactobacillus reuteri strains have probiotic functions in their modulation of the microbiota and immune system in intestines. In this study, the effects of L. reuteri LR1, a new strain isolated from the feces of weaning piglets, on intestinal epithelial barrier damage in IPEC-1 cells caused by challenge with enterotoxigenic Escherichia coli (ETEC) K88 were examined. It was found that L. reuteri LR1, in large part, offset the ETEC K88-induced increase in permeability of IPEC-1 cell monolayers and decreased the adhesion and invasion of the coliform in IPEC-1 cells. In addition, L. reuteri LR1 increased transcript abundance and protein contents of tight junction (TJ) proteins zonula occluden-1 (ZO-1) and occludin in ETEC K88-infected IPEC-1 cells, whereas it had no effects on claudin-1 and F-actin expression. Using colloidal gold immunoelectron microscopy, these effects of L. reuteri LR1 on ZO-1 and occludin content in IPEC-1 cells were confirmed. By using ML-7, a selective inhibitor of myosin light-chain kinase (MLCK), the beneficial effect of L. reuteri LR1 on contents of ZO-1 and occludin was shown to be dependent on the MLCK pathway. In conclusion, L. reuteri LR1 had beneficial effects on epithelial barrier function consistent with increasing ZO-1 and occludin expression via a MLCK-dependent manner in IPEC-1 cells during challenge with ETEC K88.